2014
DOI: 10.5194/bg-11-6769-2014
|View full text |Cite
|
Sign up to set email alerts
|

Sea-ice melt CO<sub>2</sub>–carbonate chemistry in the western Arctic Ocean: meltwater contributions to air–sea CO<sub>2</sub> gas exchange, mixed-layer properties and rates of net community production under sea ice

Abstract: Abstract. The carbon dioxide (CO 2 )-carbonate chemistry of sea-ice melt and co-located, contemporaneous seawater has rarely been studied in sea-ice-covered oceans. Here, we describe the CO 2 -carbonate chemistry of sea-ice melt (both above sea-ice as "melt ponds" and below sea-ice as "interface waters") and mixed-layer properties in the western Arctic Ocean in the early summer of 2010 and 2011. At 19 stations, the salinity (∼ 0.5 to < 6.5), dissolved inorganic carbon (DIC; ∼ 20 to < 550 µmol kg −1 ) and total… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 55 publications
1
32
1
Order By: Relevance
“…Recent work on modeled Arctic sea ice has shown that during ice growth, due to CO 2 flux from sea ice to the atmosphere, sea ice is likely basic (pH > 9). During ice melt, due to the flux of CO 2 from the atmosphere to sea ice, melting sea ice becomes likely acidic (pH < 6.5), which can lead to acidic melt ponds in the Arctic (Bates et al, 2014). The acidification of the sea-ice environment has not yet been observed in Antarctica, but it is possible that net primary productivity can change the sea surface pH and therefore Fe bio-availability over a seasonal growth/melt cycle.…”
Section: Effect Of Co 2 and Ph On Fe Chemistrymentioning
confidence: 99%
“…Recent work on modeled Arctic sea ice has shown that during ice growth, due to CO 2 flux from sea ice to the atmosphere, sea ice is likely basic (pH > 9). During ice melt, due to the flux of CO 2 from the atmosphere to sea ice, melting sea ice becomes likely acidic (pH < 6.5), which can lead to acidic melt ponds in the Arctic (Bates et al, 2014). The acidification of the sea-ice environment has not yet been observed in Antarctica, but it is possible that net primary productivity can change the sea surface pH and therefore Fe bio-availability over a seasonal growth/melt cycle.…”
Section: Effect Of Co 2 and Ph On Fe Chemistrymentioning
confidence: 99%
“…Dissolution of ikaite within melting sea ice in the spring and export of this related high TA : TCO 2 ratio meltwater from the ice to the water column will decrease the pCO 2 and increase pH and aragonite of the surface layer seawater. Accordingly, during sea ice melt, an increase of aragonite in the surface water in the Arctic was observed (Chierici et al, 2011;Fransson et al, 2013;Bates et al, 2014). However, it was difficult to ascribe this increase to the legacy of excess TA in sea ice, ikaite dissolution or primary production.…”
Section: Potential Impact Of Sea Ice Growth and Ikaite Export On Aragmentioning
confidence: 99%
“…The impact of sea-ice melt itself on pCO sea 2 was difficult to resolve only from our observations. Bates et al (2014) found both basic (i.e., DIC / TA < 1) and relatively acidic (i.e., DIC / TA > 1) melt ponds in the Canada Basin. To study the impact of meltwater on carbonate chemistry, direct sampling of sea ice into gastight bags (Fransson et al, 2013) will be required.…”
Section: Variations In Carbonate Chemistry In the Surface Layermentioning
confidence: 99%
“…Although dilution of the N. Kosugi et al: Low pCO 2 under sea-ice melt in the Canada Basin surface water with meltwater lowers the partial pressure of CO 2 (pCO sea 2 ), shoaling of the surface mixed layer would accelerate equilibration of the surface water with the overlying air. The input of meltwater is also likely to influence carbonate chemistry by altering the ratio of dissolved inorganic carbon (DIC) to total alkalinity (TA), although it is still unclear whether the addition of meltwater increases or decreases the DIC / TA ratio (Rysgaard et al, 2007;Bates et al, 2014). Cai et al (2010) reported unprecedented high pCO sea 2 (∼ 370 µatm) in the Canada Basin in summer.…”
Section: Introductionmentioning
confidence: 99%